Geografi Dialek Bahasa Dayak di Kecamatan Sepauk Hulu Kabupaten Sintang Provinsi Kalimantan Barat - Rizky Oktiyadi; Ahadi Sulissusiawan; Patriantoro; Hotma Simanjuntak; Sesilia Seli (Syntax Idea)
This research on dialect geography applies a synchronic comparative linguistic approach with interpretations based on historical linguistic differentiation. The study, which focuses on phonological and lexical aspects, was conducted to determine the linguistic distance between the Dayak languages used by the people who identify themselves as Sekubang and Seberuang residing in the Sepauk Hulu District. The data presented and discussed in this study consist of responses from 21 research informants related to 829 lexical question glosses. This data was obtained through interviews conducted by the researcher with research informants in each observation area. The method used in data analysis is the synchronic comparative method, applying dialectometric formulas and inter-village triangles. The results of the data analysis, which disregards phonological differences between observation areas, show differences in dialect, subdialect, and speech. Based on the analysis and findings in this study, it can be concluded that the Sekubang and Seberuang languages are the same. However, locally, they identify themselves as separate languages. Therefore, to affirm the similarity between these two Dayak variants, the term "Seberuang language" is introduced as a replacement for the names of both languages. This designation is based on the schematic depiction of the broader Seberuang language usage area compared to the Sekubang language usage area.